A cyanobacterium, priorly stressed by chemical way, could represent the occult Tantra for tanning phototypes I and albinoes - Piotr Brzezinski; Lorenzo Martini (Our Dermatology Online, 2019)
Background: Since the recent discover of seven UV-absorbing pigments (UVP), isolated from various marine organisms and identified as a series of mycosporine-like amino acids (MAAs), that are reputed to absorb in wavelengths ranging from 310 to 365 nm, spanning both UV-B and UV-A (320-400nm) portions of the solar spectrum (mycosporine-glycine, shinorine, porphyra-334, palythine, asterina-330, palythinol, usujirene and palythene). We have made up our mind to select one cyanobacterium (Aphanothece sacrum), admitted as cosmetic ingredient, apt to increase its amount of mycosporine-2-glycine, a natural sunscreen factor among the most efficient in nature, when undergoes to chemical stresses. Material and Methods: In two group of volunteers was used a gel made up with 2 g of Aphanotece sacrum powder in 1.5% karaya gum aqueous solution was prepared and gel with 2 g of Aphanotece sacrum powder following the above mentioned method in 1.5% karaya gum aqueous dispersion. Was evaluate the capacity of the cyanobacterium to protect skin from UVB rays under long exposure to artificial sun. Results: The cosmetic that reveals a SPF equivalent to 56 is able to minimize at all the chances of burning. Phototype I may be protected exclusively by inorganic powerds (titanium dioxide, barium sulphate, kaolin etc.), and thanks to the application of gel two it is possible to have a minimal tanning. Conclusion: We have tried to treat chemically the cyanobacterium (easily available on the market, as in Japan it is considered a common foodstuff) and let it be an exceptional sunscreen, able to protect even phototype I and albinoes.